(untitled) (Bangladesh Journal of Botany, 2022)
Bioactive chemicals found in medicinal plant extracts aid in the mitigation, eradication and cure of diseases of living animals and plants. In the quest for novel medicinally significant plants, the current article focuses on determining the most successful and promising plants for suppressing tea leaf thrips (Scirtothrips bispinosus) through applying statistical model. 22 medicinal plants extraction had been used to achieve the stated goals of the study. Plant extract solutions were dissolved in their respective solvents at varied concentrations for the assessment of entomopathogenic activity, namely 1, 5, 10 and 15%. According to the Translog stochastic frontier model, the level of solution concentration has had a substantial negative influence on the mortality of tea thrips, with thrips mortality increasing dramatically as the concentration level was decreased. The technical effectiveness of the mortality showed that plant extracts and their related features were over 98 percent effective in controlling tea thrips, as opposed to chemicals and pesticides. Bangladesh J. Bot. 51(3): 401-410, 2022 (September)